Análise da eficiência energética de uma unidade habitacional em cenários de ocupação urbana em Araraquara-SP, sob a optica do RTQ-C - Costa, Orlando Pereira da (2020)
The shading caused by the built volumetry and the verticalization of buildings in an urban area, can affect the levels of human comfort. The organization of elements built to control comfort levels is a design strategy for urban space, and should be considered by the actors involved in construction, such as architects, engineers, electricians, entrepreneurs and unique users, who can change with their performance or performance . energy of the building. The surrounding elements are built, they must also be used by the designers, making the best use of natural lighting and ventilation and shading. The aim of this study is to assess the level of energy efficiency of an isolated housing unit subject to avocado shading by different urban density scenarios. The envelope protected from the interior of the building, therefore, the more exposed to the interior of the building, the greater the thermal exchange allowed between the interior and the exterior. The quality of the construction of the Envelope and its materials can increase thermal levels, causing greater heat gains in climates, higher temperatures and environmental damage, affecting the levels of environmental comfort. The method was based on the evaluation of the microclimate behavior of the Vila Harmonia resource in Araraquara SP, in the elaboration of an urban occupation scenario and in the application of the certification process certified by the Technical Quality Regulation - RTQ-C, to determine an economic method of a hypothetical housing unit, according to its classification in efficiency levels and the possible impacts of shading on its energy performance. The results showed that the environmental changes caused by possible transformations of the urban space in this case study were positive and contributed to reaching the “A” level of energy efficiency. As vertical buildings in the surroundings, they act as a great breeze, shading the roof, walls and openings. Urban environment developers can use the Methodology for Neighborhood Impact Study as a tool for new projects, thus inserting a shadow projection into horizontal or vertical housing units, using a better economic way of undertaking, and mitigating negative impacts.